Evaluation of the Cradle to Kinder programme for Aboriginal mothers and their children: perspectives from the women and their workers. (7th December 2020) - O'Donnell, Renée; Bamblett, Muriel; Johnson, Gabrielle; Hunter, Sue-Anne; Stringer, Kerry; Croisdale, Shantai; Pizzirani, Bengianni; Ayton, Darshini; Savaglio, Melissa; Skouteris, Helen
Abstract: This research was undertaken on the lands of the Wurundjeri people of the Kulin nation. We pay our respects to Elders of the past, present and emerging, and also acknowledge the generous contribution to this research made by women and their families and Victorian Aboriginal Child Care Agency (VACCA) staff. Aboriginal Cradle to Kinder (AC2K) is a home-visiting and advocacy programme focussed on promoting Aboriginal maternal and child health during both pre- and postnatal stages of parenthood which was delivered by VACCA, an Aboriginal Community Controlled Organisation. While there have been some feasibility assessments conducted on AC2K, no study to date has evaluated the impact of this programme from the perspective of neither the women nor the staff who deliver the programme. The aim of this study, therefore, was to evaluate how both the women and the staff evaluated the AC2K programme, namely the strengths, limitations and recommendations of the programme. Through consultation with VACCA, this study used a qualitative approach using interpretative phenomenological analysis to explore the processes underpinning the programme coupled with participants' experiences of the programme. A co-design process was used in the development of interview questions, and a total of seven women and six workers participated in semi-structured interviews. The results revealed three superordinate themes across both participant groups: cultural connection (i.e. how well the programme facilitates cultural connection), system complexities (i.e. caseloads, staff turnover and child protection [CP] difficulties) and programme features (i.e. parenting enhancement and unique programme benefits). The processes, and the programme more broadly, were evaluated positively by both the women and staff who supported its delivery. Specifically, a greater connection to culture, increased parenting skills and unique programme benefits were reported. However, there were recommendations on how the programme could be further strengthened, including negotiable caseloads with the Department and improved partnership with CP. These changes can help to further improve the experiences of both the women and their workers when engaging in Aboriginal specific maternal health and well-being supports.